EDUKASI COVID-19 DI SMAN 3 BENGKULU TENGAH: TINJAUAN KHUSUS PADA ADAPTASI KEBIASAAN BARU DAN URGENSI PEMENUHAN PROTEIN HEWANI: Covid-19 Education in Senior High School 3 at The Middle of Bengkulu: A Special Topic on The Adaptation of New Habits and The Urgency of Fulfilling Animal Protein - Elvira Yunita; Liya Agustin Umar; Nurmeiliasari; Diah Ayu Aguspa Dita (Forind Press, 2023)
Sar-Cov2 infection is still occurring, although in some areas there has been a decrease in infection cases. This condition has become the basis for policy makers in Bengkulu Province to issue a circular letter so that schools can be carried out face-to-face. The condition of facing the adaptation of new habits that are currently being carried out really requires good knowledge and understanding of health protocols. In addition, preventive measures from cases of infection that occur, one of which can be pursued by increasing the body's immune system through meeting the needs of animal protein. The method applied to this Community Service Program (PKM) is through interactive counseling to SMAN 03 Bengkulu Tengah and distribution of dairy products to the academic community at SMAN 03 Bengkulu Tengah. The results of this PKM show that the socialization of adaptation to new habits can provide understanding to teachers and students at SMAN 3 Bengkulu Tengah so that they can implement clean and healthy living behaviors. In addition, the provision of dairy products can be the first step in efforts to meet the needs of animal protein that supports the body's immune system. Based on the analysis of this PKM activity, continuous implementation in increasing knowledge about adapting new habits and fulfilling balanced nutrition must continue to be carried out. This is carried out to prepare the community so that they can continue their activities in the new normal conditions.